2007
DOI: 10.1007/s10531-007-9205-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity conservation in a fast-growing metropolitan area in China: a case study of plant diversity in Beijing

Abstract: As the capital of China, Beijing has experienced extensive urbanization in the past two decades. To explore the effect of urbanization on plant diversity, we investigated the vascular plant diversity of the whole Beijing Municipality in three different functional (urban, suburban and exurban) regions. For its geo-diversity, Beijing has a rather abundant vascular plant diversity (2,276 species), including 207 species of conservation concern such as endemic, threatened and protected species. The exurban region h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…Alien species in the built-up areas of Beijing accounted for 53% of all species recorded in our survey. While this percentage is close to the 54.8% of alien plant species reported by Wang et al (2007), it is much larger than the 28.6% that were recorded by Zheng and Liu (2006), a study conducted in the constructed urban areas of Beijing. It is also greater than the range of 19.3-45.7% that was found in a study of eight cities in the eastern and mid-western United States, including New York City (Clemants and Moore 2003).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Alien species in the built-up areas of Beijing accounted for 53% of all species recorded in our survey. While this percentage is close to the 54.8% of alien plant species reported by Wang et al (2007), it is much larger than the 28.6% that were recorded by Zheng and Liu (2006), a study conducted in the constructed urban areas of Beijing. It is also greater than the range of 19.3-45.7% that was found in a study of eight cities in the eastern and mid-western United States, including New York City (Clemants and Moore 2003).…”
Section: Discussionsupporting
confidence: 66%
“…While Polish villages have an average of 30% nonnative plant species, medium-sized towns have an average of 40-50%, and cities have an average of 50-70% non-natives (Kowarik 1990). Thirty three invasive species were recorded in this study, including four harmful invasive species that were previously reported in another study on the urban flora of Beijing (Wang et al 2007). These were Alternanthera philoxeroides, Conyza canadensis, Galinsoga parritlora, and Lolium temulentum.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…From 2000-2010, the increase of the built-up land area in East China was about 2.55 times the increase from 1990 to 2000. It is notable that the expanded area of built-up land with less vegetation distribution was mainly converted from semi-natural cropland, thus exerting considerable pressure on biodiversity conservation (Li et al, 2010;McDonald et al, 2008;Seto et al, 2012;Wang et al, 2007). Cropland reclamation mostly occurred in Northeast and Northwest China.…”
Section: The Main Impacts Of Land Use Changes On Biodiversity Conservmentioning
confidence: 99%
“…Accordingly, they have suggested that increased efforts should be made to protect Mediterranean-type forests and scrublands, as well as traditional agricultural practices. Wang et al (2007) analyzed the vascular plant diversity of Beijing along an urban-suburban-rural gradient, and recommended improving the structure and ecological function of green spaces in urban region, preserving as much remnant natural habitats in the suburban region, and restricting the rural tourism and establishing a biosphere reserve in the exurban region. Newmark et al (2011) conducted a multispecies analysis of the impact of habitat fragmentation on avian nest survival within an Afrotropical understory bird community.…”
Section: Introductionmentioning
confidence: 99%